Pengaruh Simpanan Pokok Dan Simpanan Wajib Terhadap Sisa Hasil Usaha Pada Koperasi Mitra Sejahtera Samarinda - Elfreda A. Lau3, Riza Suskaniah, LCA. Robin Jonathan 2, (EKONOMIA, 2015)
Effect of Principal and Savings Against Mandatory Business Profits In Samarinda Welfare Coorperative Partners. This study aims to determine whether the principal savings and mandatory savings significant effect on operating result in Samarinda Welfare Coorporative Partners. Based on the coefficients coeficients table above, it can be formulated multiple regression equation that shows the influence of the independent variables on the balance of the balance of the (Y) as follows : Y = -2,003,500.968 + 3.491 + 0.812 X1 X2 Value Constant -2003.500,968 which shows that if there is no principal factor (X1) and compulsory savings (X2), then the cooperative will impact the declining balance of the Rp. 2,003,500.968.Principal variabels (X1) 3.491 positive impact on the balance of the (Y). This indicates that the cost effect on the Prrincipal of Business. If the principal is raised Rp. 1 it will elevates Bussines Profits Rp. 3.491. This is because the Principal is the capital it self where savings can not be withdrawn as long as the customers listed as members of the coorperative.Mandatory Deposit variabe (X2) has positive influence on Business Profit (Y) of 0,812. If Compulsory deposits raise Rp. 1 it will raise the balance of the Rp. 0,812. It indicates that the variable is positive because waib savings cooperative capital paid continuously by the customer in accordance with the condition s set by the cooperative.The result of testing the effect of independent variables on the dependent variable simultaneously obtain significant value obtained 0.041 where this value is smaller than significant level that is equal to 0.050 so that simultaneous hypothesis in this study received.